2020
DOI: 10.1002/cne.24927
|View full text |Cite
|
Sign up to set email alerts
|

Central afferents to the nucleus of the solitary tract in rats and mice

Abstract: The nucleus of the solitary tract (NTS) regulates life‐sustaining functions ranging from appetite and digestion to heart rate and breathing. It is also the brain's primary sensory nucleus for visceral sensations relevant to symptoms in medical and psychiatric disorders. To better understand which neurons may exert top‐down control over the NTS, here we provide a brain‐wide map of all neurons that project axons directly to the caudal, viscerosensory NTS, focusing on a medial subregion with aldosterone‐sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 120 publications
1
53
0
Order By: Relevance
“…The onset latency of the first swallow was significantly prolonged during rhythmic jaw movements. A morphological study showed direct GABAergic projection from the CeADM to the NTS [26,27]. It is likely, therefore, that the direct input from the CeADM and the masticatory CPG of the CeADM to the NTS is involved in the extension of the onset latency of the first swallow by stimulation of the CeADM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The onset latency of the first swallow was significantly prolonged during rhythmic jaw movements. A morphological study showed direct GABAergic projection from the CeADM to the NTS [26,27]. It is likely, therefore, that the direct input from the CeADM and the masticatory CPG of the CeADM to the NTS is involved in the extension of the onset latency of the first swallow by stimulation of the CeADM.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the number of swallows induced by the SLN stimulation was reduced after microinjection of a GABA A agonist into the LRF [33]. The CeADM contains GABAergic inhibitory interneurons [26,27,34]. GABAergic inputs from the CeADM and the masticatory CPG of CeADM may inhibit activation in the ventral region of swallowing CPG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PVH has distinct input and output connections that participate in various brain functions. PVH vglut2 neurons are connected to the BF 41 , and PVT 42 , and project to the nucleus of the solitary tract (NTS) 43 , lateral parabrachial nucleus (L-PBN) 16,17 , pre-locus coeruleus (pLC) 31 and ventral lateral septum (LSv) 33 . Our present ndings identi ed two speci c neural circuits, among which the PVH vglut2 →PB/LSv circuit rather than the PVH vglut2 →NTS circuit was required for the maintenance of physiological wakefulness.…”
Section: Discussionmentioning
confidence: 99%
“…The area postrema (AP) is a circumventricular organ located within the medulla oblongata below the fourth ventricle, and is, like the hypothalamus, able to detect circulating chemical messengers in the blood and transduce them into neural signals and networks, relaying information to other brain areas [1]. Adjacent to the AP is the nucleus tractus solitaris (NTS) consisting of a collection of subnuclei which receive direct inputs from multiple locations including gustatory information from cranial nerves, and postprandial signals via vagal afferents [2], and thus acts as a visceral sensory relay station within the brain.…”
Section: Introductionmentioning
confidence: 99%